“THERE IS NO GOD BUT ALLAH”: An Indonesian-Christian Reading on Miroslav Volf’s “Allah: A Christian Response” - Abdiel Harmakaputra, Hans (Jurnal Amanat Agung, 2013)
“THERE IS NO GOD BUT ALLAH”: An Indonesian-Christian Reading on Miroslav Volf’s “Allah: A Christian Response”